Hypoglycemic and Hypolipidemic Effect of Sida rhombifolia ssp. retusa in Diabetic Induced Animals - Kamlesh Dhalwal; Vaibhav M. Shinde; Bhagat Singh; Kakasaheb R. Mahadik (International Journal of Phytomedicine, 2010)
In the present study, the anti-diabetic effect of aqueous extract of Sida rhombifolia ssp. retusa (Malvaceae) leaves was studied in normal and streptozotocin (STZ)-induced (60 mg/kg, single intraperitoneal injection) diabetic rats. Hypoglycemic activity in normal rats was tested after administration of 200 mg/kg of extract. Aqueous extract showed a 15% reduction in plasma glucose level after 1.5 h of extract administration. When tested in STZ-induced diabetic rats the reduction in plasma glucose was 17%. In oral glucose tolerance test in normal rats and STZ-induced rats the decrease in AUC was 15 and 7% respectively. Glibenclamide was used as reference drug and showed significant hypoglycemic effects in normal rats but had marginal activity in STZ-induced diabetic rats. In hypolipidemic study a dose of 200 mg/kg of aqueous extract has shown reduction in triglycerides (TG) (16%), cholesterol (4%), and glucose level (10%). Fenofibrate was used as standard drug for hypolipidemic study. The results obtained from the experiment provided scientific evidence in favor of the traditional use of Sida rhombifolia ssp. retusa leaves for the treatment of diabetes mellitus.